Anodal tDCS of contralesional hemisphere modulates ipsilateral control of spinal motor networks targeting the paretic arm post-stroke. (April 2022) - Klomjai, Wanalee; Giron, Alain; Mounir El Mendili, Mohamed; Aymard, Claire; Pradat-Diehl, Pascale; Roche, Nicolas; Katz, Rose; Bayen, Eléonore; Lackmy-Vallee, Alexandra
Highlights: Anodal transcranial direct current stimulation was applied over the undamaged hemisphere in hemiparetic stroke subjects. The aim was to explore effects induced by stimulation of the undamaged motor cortex in spinal motor networks. Activation of the undamaged hemisphere reveals an ipsilateral control onto spinal motor networks of the hemiparetic side. Abstract: Objective: The role of ipsilateral motor cortex efferent pathways in the transmission of voluntary command to spinal motor nuclei remains controversial in humans. In healthy subjects, their implication in cortical control is hidden by predominant role of crossed corticospinal tract. However, evidence from electrophysiological and imaging studies suggest that ipsilateral tracts may contribute to functional recovery after unilateral brain damage. This randomized-sham control study aims to explore to what extent ipsilateral tracts from the undamaged hemisphere may strengthen corticospinal control onto spinal motor networks following stroke. Methods: Anodal transcranial direct current stimulation (tDCS) was combined with monosynaptic H-reflex method to evaluate the variations of reciprocal inhibition (RI) in wrist flexors in 21 stroke participants. Results: Anodal tDCS decreased RI in wrist flexors in stroke participants in both arms. tDCS unmasks an ipsilateral control from the undamaged hemisphere onto spinal motor networks controlling affected arm muscles in stroke participants. In the unaffected (contralateral) arm, effects in stroke participants were opposite to those induced in healthy subjects. Conclusions: Stimulation of the undamaged cortex in stroke participants induces modulation of ipsilateral motor networks controlling the hemiparetic side. Significance: Rehabilitation could leverage stimulation of the undamaged hemisphere to enhance motor recovery post stroke.